Europa und Palästina 1799-1948 : Religion - Politik - Gesellschaft = Europe and Palestine 1799-1848 : religion - politics - society - Haider-Wilson, Barbara; Trimbur, Dominique (2010)
The encounter of Occident and Orient is one of the major topics of our time. This encounter is the theme of the present volume in regards to the Palestinian realm from 1799 to 1948. The contributions of twelve authors from Germany, France, Israel, Italy, Austria, Russia, and Switzerland are concerned with a period in which the ordinary interest for the land of the Bible and Christian history was connected to a much greater cultural and political discourse, which was not only carried out by the western churches, but also by European societies in general. In nineteenth- and early twentieth-century Palestine, many forces were at work; from 1516/17 Palestine belonged to the Ottoman Empire. Beginning in the nineteenth century, especially after 1840, this small territory became an issue for world politics. The maintenance of the integrity of the Ottoman Empire constituted one of the guidelines of the European powers.